RISK TAKING BEHAVIOURS SUSCEPTIBLE TO PSYCHO-SOCIAL FACTORS: A STUDY OF ADOLESCENTS IN SOKOTO METROPOLIS, NIGERIA - S. Y. Tsagem, PhD, A. I. Gaata, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The study explored the influence of moderating variables of gender, age, family type and religious affiliation on adolescents’ risk-taking behaviours. Thus, the study employed a descriptive survey method, where a total of 384 married adults were selected through simple random sampling techniques. The participants responded to a questionnaire designed by the researchers titled ‘Risk Taking and Parental Monitoring Questionnaire (RTPMQ)”. The content and construct validities of the instrument was adjudged by a team of experts from the Department of Educational Foundations in Usmanu Danfodiyo University, Sokoto. The reliability of the instrument was established using internal consistency method which yielded a coefficient of 0.78. Data collected was analyzed using both descriptive and inferential statistics; thus, for the demographic data, percentage was employed while an independent t-test and ANOVA statistical tools were employed to test the hypotheses at 0.05 level of significance. Results reveal no difference in gender, age, family type and religious affiliation in risk-taking behaviours among the adolescents. One of the recommendations made was that the family and the society should ensure effective and efficient training, proper upbringing, equal treatments and empowerment in order to apprehend adolescents’ risk-taking behaviour.